INDEFINITENESS AND DEFINITENESS IN WAIJEWA - I Wayan Budiarta; Ni Wayan Kasni (Linguistik Indonesia, 2023)
This study aims to find out how Waijewa, a minority language in Sumba, East Nusa Tenggara, differentiates between definite and indefinite noun phrases. The data were taken from structured interviews with four informants who speak Waijewa language as well as documentation. This study revealed that the indefinite noun phrase in Waijewa language is conveyed by zero article. The definite noun phrases are marked by using the demonstratives ne ‘this’, nati/neti ‘that’, na ‘that’, hidda ‘these’, and heida ‘those’, genitive case, and definite emphasizing clitics, such as {-wa} ‘that’, {-we} ‘this’, {-wi} ‘these’, ‘those’. The particle pais also used to convey the definiteness of a noun with a family status as father, mother, or uncle. The reference is anaphoric. However, the reference can be cataphoric when the noun phrase has a definite emphasizing marker functioning to emphasize the referent meant by the speaker.